Tann- og munnstell hos eldre i institusjon - Andreassen, Therese; Rist, Ingeborg; Solstrand, Tina (UiT Norges arktiske universitet, 2016)
Many studies show that the daily oral hygiene habits and dental care of elderly patients in nursing homes, are not satisfactory and that this poses a risk for both oral and general health. A growing number of seniors have kept their own teeth, and will be a large group of patients for us to treat as future dentists. The aim of this study was to survey attitudes exist among dental and nursing staff regarding the oral health of institutionalized elderly patients. We collected relevant articles from journals for dental personnel published during the last decade in Norway, Sweden, and Denmark. To gain even more knowledge, we chose to interview nursing staff at two different nursing homes and dental staff at two dental clinics, in two municipalities in Northern Norway. The content of the articles was used as basis for the interviews. The results showed that the daily routines for dental care were relatively similar in the two nursing homes. However, there were differences in regards to how the equipment cost for oral care was covered. The nurses were satisfied with the guidance and teaching they received from the dental hygienists, but they wished to have more knowledge about oral health and related factors. The dental hygienists felt they needed more time to work with both patients and staff in the nursing homes. The co-operation between the dental clinic and the nursing home was considered to be good in one of the municipalities, but challenging in the other one. In the last case, the residents of the nursing home had greater treatment needs than in the other nursing home. We conclude that the nursing staff felt they had enough time to help the patients with proper daily oral hygiene routines, but they needed more knowledge about oral health. The dental hygienists believed that co-operation between the dental clinic and nursing home could be improved.